Desarrollo de germoplasma nativo de Lippia integrifolia (Gris.) Hier : una especie de importancia aromática y medicinal - Iannicelli, Jesica (2016)
In Argentina aromatic and medicinal plants have been traditionally harvested from the wild and without any major limitation provoking an important erosion of germplasm. Lippia integrifolia is one of the species under this situation. To prevent the progress of this process, it would be important to change the extractive model for a production paradigm. A possible strategy is to generate and transfer to collectors/producers, genetically improved materials. Combination of in vitro tissue culture techniques with autopolyploidy have brought advantages for the improvement of the production of secondary metabolites. In this work, successful induction of polyploidy in L. integrifolia was achieved and the autotetraploids showed significant differences from the field mother plant (size of the leaves, inflorescences, trichomes, stomatas, and pollen grains). In addition, essential oil yields were enhanced in tetraploids, and quantitative differences were detected in the composition of all individuals recovered from in vitro culture (tetraploids and diploids) with respect to the mother. field plant. Moreover, genetic variability (polymorphisms) was detected in all ex vitro plants (diploids and tetraploids).\nDue to the phenotypic differences found (higher sizes of the used portion), a tetraploid individual became a new variety of incayuyo.